E- LEARNING PEMBELAJARAN KIMIA BERBASIS WEB DI SMK ISLAMIC CENTRE BAITURRAHMAN SEMARANG (Information Technology and Telematics, 2013)
AbstractSMK Islamic Centre Baiturrahman Semarang that lies in Abdul Rahman Saleh street No.285 Semarang, is one of vocational high school which is never been using online learning system as before. They use conventional learning system by meetingand teaching directly between the teacher and the students in classroom along this time. The purpose of creating e-learning web is to design web-based e-learning, especially in chemistry in order to increase learning motivation of the students. The analysis devices which are used to design this e-learning system are UML (Unified Modeling Language) that uses for showing use case diagram, sequence diagram and class diagram; MOODLE (Modular Object-Oriented Dynamic Learning Environment) as the developing system software, Web Server, Database Server and PHP that is fulfilled of XAMPP. The application that will be created is possible to give the points of chemistry and also give some questions for the students.The result of this research is there have developed learning system of chemistry that uses web-based system using MOODLE as the developing system software. This system is possible to save points of chemistry in formats such as PDF file, power point, examples of animation are suitable to the subject and give questions which can be also giving correction and score automatically.Key words: E-learning, SMK, Web, Enterprise Architect, UML, Chemistry, PDF